The analysis of the epistolario family martiano: their synergy with the categories text, epistolary text, text epistolary family martiano, reading and analysis in the process of teaching-learning of the Spanish language - Arianne Ortega-Vega; María Fidelia Díaz-Reyes; Odalis Lorié-González (Maestro y Sociedad, 2018)
This article presents a critical analysis of the analysis of the family Epistolary Martí in the process of teaching learning the Spanish language in the formation of primary teachers and the systemic perspective in the treatment of this content from the Synergy that is established between the categories text, text epistolary, text epistolary familiar Martí, reading and analysis, propositions that emerge in the context of the search for the specificity for the analysis of the family letters written by José Martí, In a process where the teacher in training acquires methodological didactic tools by assuming a bifunctional role: Learn to learn and learn to teach. It emphasizes the necessity of selection of procedures developers as essential condition for the development of its cognitive competence, communicative sociocultural having as premise the active character with which it assumes the process of analysis. It presents, a brief example of statements or activities for the analysis of a text epistolary familiar Martí.